LIQUID: treatment of high-grade dural arteriovenous fistulas with Squid liquid embolic agent$da prospective, observational multicenter study - Vollherbst, Dominik; Boppel, Tobias; Wallocha, Marta; Berlis, Ansgar; Maurer, Christoph J.; Weber, Werner; Fischer, Sebastian; Bock, Alexander; Meckel, Stephan; Bohner, Georg; Liebig, Thomas; Herweh, Christian; et al. (Journal of neuroInterventional surgery, 2023)
Background Endovascular embolization is a feasible treatment for cranial dural arteriovenous fistulas (DAVFs). New embolic agents aim to improve the success of DAVF embolization. - Objective To assess the safety, efficacy, and short-term outcome of the treatment of DAVFs using the new liquid embolic agent Squid. - Methods The LIQUID study is a prospective, observational multicenter study on the treatment of high-grade (Cognard type ≥3) DAVFs with the embolic agent Squid. The primary outcome measures were safety (ie, morbidity and mortality), as well as the occlusion rate 90 to 180 days after treatment. - Results In eight centers, 53 patients (mean age 59.8 years, 22.6% female) were treated in 55 treatment sessions. Of the DAVFs, 56.6% were Cognard type III, 41.5% type IV, and 18.9% were ruptured. Squid 18 was used in 83.6% and Squid 12 in 32.7% of the treatments. The overall rate of intraprocedural or postprocedural adverse events (AEs) was 18.2%. Procedure-related AEs resulting in permanent morbidity were observed in 3.6%. One patient (1.8%) died unrelated to the procedure due to pulmonary embolism. The final complete occlusion rate at 90 to 180 days was 93.2%. After a mean follow-up of 5.5 months, the modified Rankin Scale (mRS) score was stable or improved in 93.0%. In one of the patients, worsening of the mRS score was related to the procedure (1.8%). - Conclusion Squid is a safe and effective liquid embolic agent for the treatment of high-grade DAVFs.